SAT0010 FUNCTIONAL BIOMARKER DEVELOPMENT FOR CELL-BASED THERAPY IN RHEUMATOID ARTHRITIS. (June 2019) - Breitman, Maya; Bonfield, Tracey; Lasalvia, Susan; Lazarus, Hillard; Caplan, Arnold; Singer, Nora
Abstract : Background: Rheumatoid Arthritis (RA) is an autoimmune disease in which early treatment prevents joint damage. Autoantibodies such as rheumatoid factors (RF) and anti-citrullinated peptide antibodies (APCA) define a subset of RA patients at the highest risk for damage. Reduction of RA disease activity is associated with improvement in function(s) of regulatory T cells (Treg) and attenuated responses of pro-inflammatory T effector cells (Teff). Human Mesenchymal Stem Cells (hMSC) isolated from bone marrow and culture-expanded have strong immunomodulatory properties; we hypothesize that therapeutic use of hMSCs may skew the immune system to resemble its pre-RA state. Lack of available biologic correlates measured early-on that indicate response to treatment limits efficacy assessment of cell-based therapy. Use of clinical response criterion requires large numbers of patients and may be impractical in early stage clinical trials. This work was performed in anticipation of conducting a Phase I safety trial of cell-based therapy in early RA. Objectives: We set out to develop functional assay(s) as biomarkers of response that would indicate early-on that hMSC were or were not modulating immune function in a manner that could potentially predict potency and efficacy in RA patients. Methods: Sero-positive female patients with active early RA (RAPID 3 avg 5.7/10 (high severity)) and healthy donor age and sex-matched controls were enrolled. Second passage bone marrow hMSCs were obtained from healthy donors < 30 y.o. (Case Comprehensive Cancer Center Hematopoietic Biorepository and Cellular Therapy Core). Peripheral blood CD4+ T cells were stimulated by cross-linking CD2/CD3/CD28 for 5 days. CD4+ T-cell proliferation rates were measured, and suppression indices calculated by comparing proliferation indices of CD4+ T-cells cultured with and without hMSC-conditioned medium. Results: hMSC-related suppression 32.2 ±7.8 (mean +/- SE) percent in RA CD4+ T-cells compared to 45.7± 8.9 percent for healthy donors CD4+ T-cells. We demonstrated that soluble products from hMSCs can inhibit proliferative responses of CD4+ T cells from patients with active RA though the studies were not powered to detect differences between RA and healthy donors. With limited number of early RA patients, correlation between level of MSC-related suppression and antibody status were not possible. That being said, the data trend appears promising. Conclusion: Our ex vivo experiments demonstrated that MSCs may be suppressive in RA as well as in healthy donors. To our knowledge, this study is the first demonstration of the potential for using ex vivo suppression assays to predict response to cell-based therapy in early RA. Such assays might be performed to predict the efficacy of selected hMSCs to treat RA. Acknowledgement: This study was supported by David and Virginia Baldwin Foundation, and by the Clinical and Translational Science Collaborative of Cleveland, 4UL1TR0002548 from the National Center for Advancing Translational Sciences (NCATS) component of the National Institutes of Health and NIH roadmap for Medical Research. Its contents are solely the responsibility of the authors and do not necessarily represent the official views of the NIH. Disclosure of Interests: None declared